2004
DOI: 10.1016/j.jacc.2004.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac events in patients with negative maximal versus negative submaximal dobutamine echocardiograms undergoing noncardiac surgery

Abstract: In patients undergoing preoperative DSE, failure to achieve target HR is not uncommon despite an aggressive DSE regimen. A negative DSE without resting WMAs has excellent NPV regardless of the HR achieved. Patients with resting WMAs appear to be at increased risk for perioperative events even without provokable ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…No MACE occurred in patients without preoperative ischemia, whereas 43% of those with ischemia at low workloads had MACE. In a separate study of 429 participants, dobutamine stress echocardiography had an excellent negative predictive value (98%) for perioperative MACE …”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…No MACE occurred in patients without preoperative ischemia, whereas 43% of those with ischemia at low workloads had MACE. In a separate study of 429 participants, dobutamine stress echocardiography had an excellent negative predictive value (98%) for perioperative MACE …”
Section: Methodsmentioning
confidence: 96%
“…Among patients with poor functional capacity (<4 METs) at higher risk for noncardiac surgery, exercise testing with cardiac imaging or noninvasive pharmacological stress testing (either dobutamine stress echocardiography or vasodilator stress myocardial perfusion imaging) to assess for myocardial ischemia is only reasonable if the results from this testing would change perioperative medical management and decisions regarding coronary revascularization . European guidelines recommend stress testing with imaging before high-risk surgery in patients with more than 2 clinical risk factors (using the Revised Cardiac Risk Index) and poor functional capacity (<4 METs) and treatment according to clinical indications independent of surgery .…”
Section: Methodsmentioning
confidence: 99%
“…The presence of scar in our study population was shown to have important implications for prediction and freedom from MACE. Utilization of either DSE for wall otion abnormalities or by cardiac magnetic resonance imaging by late gadolinium enhancement for presence of scar, have recognized that presence of scar with or with out ischemia is associated with approximately 4 -11 fold hazards increase risk for MACE and death [3,[19][20][21][22][23][24]. Our study reconfirms this finding, demonstrating presence of scar by DSE carries an increase risk of all cause death and combined MACE for obese African Americans; similarly, presence of scar on DSE in the general population has been associated with adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nenhum evento cardiovascular adverso maior (MACE) ocorreu em pacientes sem isquemia pré-operatória, enquanto 43% daqueles com isquemia em baixas cargas de trabalho tiveram MACE. Em um estudo separado com 429 participantes, a ecocardiografia sob estresse com dobutamina teve um valor preditivo negativo relevante (98%) para MACE perioperatório 68 . O teste de estresse de rotina não é indicado para pacientes de baixo risco, que incluem aqueles com excelente capacidade funcional e com capacidade funcional moderada a boa.…”
Section: Avaliação Da Capacidade Funcional E Teste De Estresse Para I...unclassified
“…As diretrizes canadenses não recomendam o teste de esforço préoperatório e o teste de exercício cardiopulmonar, devido a dados limitados que apoiam os testes 64 . Entre os pacientes com baixa capacidade funcional (<4 METs) com maior risco de cirurgia não cardíaca, o teste ergométrico com imagens cardíacas ou teste de estresse farmacológico não invasivoecocardiografia sob estresse com dobutamina ou imagens de perfusão miocárdica sob estresse com vasodilatadorpara avaliar isquemia miocárdica seria apenas considerado se os resultados alterassem o manejo médico perioperatório e as decisões relativas à revascularização coronariana 3,67,68 . As diretrizes europeias, por sua vez, recomendam testes de estresse com exames de imagem antes de cirurgias de alto risco em pacientes com mais de 2 fatores de risco clínicosutilizando o Revised Cardiac Risk Indexe baixa capacidade funcional (<4METs) e tratamento de acordo com indicações clínicas independentes de cirurgia 5 .…”
Section: Avaliação Da Capacidade Funcional E Teste De Estresse Para I...unclassified